2023
DOI: 10.1007/s00415-023-11819-7
|View full text |Cite
|
Sign up to set email alerts
|

A hypoarousal model of neurological post-COVID syndrome: the relation between mental fatigue, the level of central nervous activation and cognitive processing speed

Abstract: Background Knowledge on the nature of post-COVID neurological sequelae often manifesting as cognitive dysfunction and fatigue is still unsatisfactory. Objectives We assumed that cognitive dysfunction and fatigue in post-COVID syndrome are critically linked via hypoarousal of the brain. Thus, we assessed whether tonic alertness as a neurocognitive index of arousal is reduced in these patients and how this relates to the level of central nervous activation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 77 publications
0
3
0
Order By: Relevance
“…found a persistent deficit in perceptual processing speed in patients with PCC with cognitive complaints. 10 , 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…found a persistent deficit in perceptual processing speed in patients with PCC with cognitive complaints. 10 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…This has been reported in several investigations conducted in both acute and chronic phases of COVID-19, especially in those with self-reported cognitive symptoms. 6 , 7 , 8 , 9 , 10 , 11 , 12 However, due to the lack of consensus on the precise definition of PCC 13 , 14 and vast differences in cognitive task design and administration, it remains unclear whether PCC is associated with generalised cognitive slowing.…”
Section: Introductionmentioning
confidence: 99%
“…30 In addition, Martin et al found a deficit in perceptual processings speed in PCC patients with cognitive complaints. 10…”
Section: Discussionmentioning
confidence: 99%
“…Given the high prevalence of PCS, the suitability of conventional, clinically established tests for disclosing processing speed deficits would be of great practical significance. Second, in our preceding study [12], we were not able to assess whether cognitive domains other than processing speed are also affected by the underlying arousal deficit. A demonstration that processing speed is selectively impaired in PCS patients would bear strong support for our hypoarousal model.…”
Section: Introductionmentioning
confidence: 93%
“…Recently, we proposed that fatigue is caused by hypoactivity within the brain's arousal network, reflected by a fundamental slowing of processing speed in PCS patients [12]. In particular, the variance of (visual) processing speed in a laboratory task was explained by a neurophysiological measure of central nervous arousal, i.e., pupillary unrest, and the level of subjective mental fatigue.…”
Section: Introductionmentioning
confidence: 99%